Regulation of resveratrol O‐methyltransferase gene in pterostilbene defensing the sour rot of wine grape. Issue 11 (26th August 2019) - Ren, Xueyan; Zhang, Xue; Zhai, Xin; Deng, Rongrong; Meng, Jiahui; Li, Xingyan; Kong, Qingjun
Abstract: Sour rot, caused by Geotrichum citriaurantii ( G. citri-aurantii. ), is one of the most serious grapevine secondary infection diseases in China. We have determined that pterostilbene, the most important phytoalexin, effectively inhibits the activity of G. citri‐aurantii. To study the synthesis mechanism of pterostilbene against G. citri‐aurantii in grape, we initially detected the content of pterostilbene present in grapes infected by G. citri‐aurantii with the use of UHPLC‐QQQ‐MS 2 . Pterostilbene levels are controlled by the resveratrol O‐methyltransferase (ROMT) gene, and within grape samples is positively related to the accumulation of resveratrol. The pPIC9k‐ROMT vector and plasmid pCAMBIA2300‐GFP‐ROMT were constructed for expression purposes. The pPIC9k‐ROMT vector was expressed in Pichia pastoris GS115 and plasmid pCAMBIA2300‐GFP‐ROMT was expressed in onion. Analysis of qRT‐PCR amplification samples revealed that gene expression was induced rapidly in grape as a defense against G. citri‐aurantii . Western blot analysis verified that the recombinant protein was successfully expressed. Practical applications: Pterostilbene is a trace and efficient phytoalexins produced by plant' secondary metabolism, which exhibits good pharmacological activity. As an important protective agent in plants, it can improve the antioxidant capacity and resistance to adversity of plants. However, the method which could be used for mass production of pterostilbene has not been reported currently. The key gene of pterostilbene biosynthesis was investigated and verified in this paper, which provides the theoretical basis for the industrial production of pterostilbene. The study of pterostilbene is significant for the prevention and treatment of G. citri‐aurantii disease, and has important practical applications for the development and production of pesticides.